Methodological Considerations and Effectiveness for Ecologically Valid Mental Fatigue Inducement in Sports: A Systematic Review - Chao Bian; Suzanna Russell; Ana Mali; Elke Lathouwers; Kevin De Pauw; Jelle Habay; Špela Bogataj; Bart Roelands (Sports Medicine - Open)
Abstract Background Mental fatigue (MF) in sports has developed from well-controlled laboratory-based studies to applied studies with greater ecological validity. Ongoing developments in the representativeness of MF inducement approaches, including the broad range of sport-specific motor tasks to simulated real-life scenarios, have shown methodological variability and inconsistent outcomes of effectiveness. Evaluating and comparing these approaches is essential to provide recommendations for designing inducement tasks in future research and considerations for practitioners. Therefore, the systematic review aimed to summarize more ecologically valid MF-inducing tasks in representative sports contexts and to evaluate the MF inducement effectiveness via manipulation check outcomes and potential after effects on subsequent sport-specific performance. Methods The review was registered on the PROSPERO database (CRD42024577183). PubMed, Web of Science, PsycINFO, and SPORTDiscus were searched until 21 August 2024 for studies that applied acute, more ecologically valid MF-inducing tasks within sports-specific contexts. The MF inducement task design and effectiveness across representative sports and participants were investigated. Results Twelve papers were included. Only a quarter of studies presented an overall low risk of bias. The 20-minute sports-specific motor tasks with cognitive demands and most 30-minute simulated real-life scenarios (i.e., social media use on smartphones, watching tactical videos, sports-themed videogame play) successfully induced MF in differing athlete samples. Ineffective MF inducement was attributed to shorter task duration, passive engagement with sparse cognitive demands, or the involvement of less susceptible participants. Conclusions This systematic review evaluated MF inducement methodologies with greater ecological validity to sporting contexts. The inducement effectiveness varied within four task types. Athletes and sports practitioners should carefully manage the modality and content of pre-competition activities to minimize MF. Future research should refine and co-design the MF-inducing task with practitioners based on multifaceted MF evidence from laboratory and real-life settings, create immersive scenarios that can better replicate the inducement process in specific contexts, and improve measurement tools, which will provide comprehensive evaluation and verification of the MF inducement.